Determinación de metales y características fisicoquímica del fango termal procedente de Cachicadán, Noviembre-Diciembre 2018 - Urtecho Benites, Roger Hugo (2018)
The use of thermal mud in different rural places of our country by the population in most times by tradition, or empirically, makes necessary studies to contribute to the safety of their use. The metals and physicochemical characteristics of the thermal mud from Cachicadán, November-December 2018, were determined. The Atomic Absorption Spectrophotometry method was used with metal flame, LOD for humidity, Incineration for ashes, Gravimetry and Volumetry for Density, Potentiometry for pH , Optical Microscopy with Neubauer Chamber for particle size, Equation proposed by Armijo F, 2015 for Ash / Weight, Specific Heat and Thermal Conductivity. The concentration determined for Fe, Ca, Zn, Ag, Cu, Hg, As, Cd, Cr, Pb metals was 7202,3; 695,86; 47,42; 27,16; 11,65; 174,81; 848,12; 2,34; 19,3; 64,5 ppm respectively. The average value of the physicochemical characteristics for Humidity, Temperature, Ash, Density, pH, Fine and Coarse Particle Size, % ash /% weight of the solid, Specific Heat, Thermal Conductivity was 71,53%; 64°C; 26,74%; 1,27 g / mL; 5,96; 1,62 μm; 4,60 μm; 0,96; 3,10 J / (kg.K); 0,45 W / (K.m) respectively